Antisolvent Separation of Thermally Cracked Vacuum Resid - Xu, Hui; Xu, Zhiming; Sun, Xuewen; Xu, Chunming; Chung, Keng H; Zhao, Suoqi (Energy & fuels, 2013)
Thermal cracking of Venezuela vacuum residue (VR) was carried out in a batch reactor system. The thermally cracked resid was diluted with toluene and was subject to antisolvent (SAS) separation using n-pentane at the liquid and supercritical state in a continuous SAS apparatus. The SAS-derived liquid and solid products were obtained and subjected to elemental and saturates/aromatics/resins/asphaltenes (SARA) analyses. The SAS liquid products are comprised predominantly of saturates and aromatics, whereas SAS solids consist of asphaltenes and toluene insolubles (TIs). The resin content of SAS liquid and solid products varies with the thermal cracking severity. As the thermal cracking severity increases, the yield of SAS liquid decreases. The saturate content in the SAS liquid increases at the expense of resin content. The TI content of SAS solids increases as the thermal severity increases. The sulfur, nitrogen, and Conradson carbon residue (CCR) contents of SAS liquid increase and the hydrogen-to-carbon (H/C) ratio and metal (nickel and vanadium) contents of SAS liquid decrease with thermal cracking severity. Physical characterization of SAS solids was conducted, indicating that the SAS solids consist of submicrometer amorphous granules when the SAS process was operated at low temperatures but form aggregates at high SAS process temperatures. As the resid concentration of SAS feed decreases, the quality of SAS liquid decreases, and the size of the SAS granules decreases. The results from this work showed that it is viable to use the SAS process to separate the heavy fraction from the thermally cracked resid.